Flow‐Cytometry‐Based Method to Detect Escherichia coli and Shigella Spp. Using 16S rRNA‐Based Probe. Issue 1 (1st February 2017) - Xue, Yong; Wilkes, Jon G.; Moskal, Ted J.; Williams, Anna J.; Cooper, Willie M.; Buzatu, Dan A.
Abstract: Detection of microbial contamination in foods before they go on to the market can help prevent the occurrence of foodborne illness outbreaks. Current methods for the detection of Escherichia coli are limited by time‐consuming procedures, which include multiple culture incubation steps, and require several days to get results. This unit describes the development of an improved rapid flow‐cytometry‐based detection method that has greater sensitivity and specificity. This method requires less time‐to‐results (TTR) and can detect a small number of E. coli in the presence of large numbers of other bacteria. Clear step‐by‐step protocols for cell concentration determination, sample preparation, and flow cytometric analysis are provided. © 2017 by John Wiley & Sons, Inc.